System poznawczy jako system reprezentacyjny - Żegleń, Urszula (Filozofia Nauki, 2005)
The main thesis of the paper is very simple, namely that the cognitive system is a representational system. The cognitive system will be defined as a system which is able to realize cognitive functions such as perception, symbolic thinking, understanding and reflection. Such a system is further characterized as: cognitively open and at the same time relatively isolated, representational, structurally complex and many-dimensional, dynamic and having functional plasticity (cognitively adaptive) and also having the capacity for self-determination. The analysis will be focused on the characterization of representation (which will be defined as a certain kind of content) and on the types of representations in the cognitive system (i.e. perceptual and conceptual representations, the representation of the body and the representation of "self").